Factors Associated with using Hearing Aid More Than 8 Hours Per Day in Patients with Hearing Disability - Chit-uea-ophat, Chonthicha; Kasemsiri, Pornthep (Srinagarind Medical Journal, 2024)
Background and Objective: Identifying factors associated with using hearing aid can help predict usage patterns. These factors could reduce resource wastage and facilitate prioritization strategies for hearing aid services. This study aimed to investigate the factors affecting hearing aid usage for more than 8 hours per day compared to those who use them for ≤8 hours per day. Methodology: A cross-control study was conducted among patients with hearing disability using hearing aids for a minimum of 6 months at Chaiyaphum Hospital between October 1, 2021 and August 31, 2022. Data were collected from medical records. The patients were divided into two groups equally as cases use hearing aids more than 8 hours and control used them ≤8 hours/day to analyze the different factors affecting their using of hearing aids. Results: Among 126 patients with hearing disability, statistically significant differences were observed between the two groups in several factors, including age, duration of hearing problems, history of previous using hearing aids, average hearing loss in the worse ear, average speech reception threshold in the better ear, and average speech discrimination score in the worse ear. Multivariable logistic regression analysis showed that only age ≤ 60 years (AOR 7.66, 95% CI 1.63-35.99), history of previous hearing aid usage (AOR 3.91, 95% CI 1.59-9.59), and average hearing loss in the worse ear greater than 70 dB HL (AOR 4.73, 95% CI 1.33-16.75) significantly influenced using hearing aids for more than 8 hours. Conclusion: Age ≤ 60 years, a history of previous using of hearing aids, and an average hearing loss in the worse ear greater than 70 dB HL are factors associated with using hearing aids more than 8 hours per day. These findings can assist in prioritizing resources and manpower during shortages and help reduce government revenue loss from underutilization.